2008
DOI: 10.1085/jgp.200810007
|View full text |Cite
|
Sign up to set email alerts
|

A Carboxy-terminal Inter-Helix Linker As the Site of Phosphatidylinositol 4,5-Bisphosphate Action on Kv7 (M-type) K+ Channels

Abstract: Members of the KCNQ (Kv7) family of voltage-gated K + channels underlie " M-type " K + currents in many different types of neurons, delayed-rectifi er currents of the heart, and K + transport channels of the inner ear and epithelia ( Jentsch, 2000 ;Robbins, 2001 ). Neuronal M currents play strong roles in regulating excitability and neuronal discharge, and their modulation by several receptors linked to the G q/11 class of G proteins endows them with powerful effects on the function of excitable cells ( Delmas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
121
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(136 citation statements)
references
References 61 publications
15
121
0
Order By: Relevance
“…Different regions endowed with clusters of basic residues have been proposed to interact with PIP 2 . Hernandez et al, identified a conserved cluster of basic residues within the linker connecting helix A and B in the C-terminus of KCNQ2-KCNQ4 subunits (Hernandez et al, 2008). This basic cluster was suggested to interact with PIP 2 through electrostatic and hydrogen-bonding networks (Hernandez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different regions endowed with clusters of basic residues have been proposed to interact with PIP 2 . Hernandez et al, identified a conserved cluster of basic residues within the linker connecting helix A and B in the C-terminus of KCNQ2-KCNQ4 subunits (Hernandez et al, 2008). This basic cluster was suggested to interact with PIP 2 through electrostatic and hydrogen-bonding networks (Hernandez et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hernandez et al, identified a conserved cluster of basic residues within the linker connecting helix A and B in the C-terminus of KCNQ2-KCNQ4 subunits (Hernandez et al, 2008). This basic cluster was suggested to interact with PIP 2 through electrostatic and hydrogen-bonding networks (Hernandez et al, 2008). However, a recent study showed that this linker is not required for PIP 2 regulation of KCNQ2 (Aivar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CaM regulatory mechanisms that change the gating behavior proceed through an effect on sensitivity to PIP 2 (Kosenko et al, 2012;Kosenko and Hoshi, 2013;Zaydman et al, 2013;Kang et al, 2014). The interlinker between helices A and B is not essential for function, although it plays a critical role in PIP 2 regulation for Kv7.3, but not in Kv7.1 and Kv7.2 channels (Hernandez et al, 2008;Aivar et al, 2012;Sachyani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies supported that PIP 2 also interacts directly with voltage-gated potassium (Kv) channels (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Several positive residues that may be critical for PIP 2 activity have been identified (7,11,18,(20)(21)(22)(23)(24). Previous studies on Kv1.2 and Shaker channels showed that PIP 2 exerts opposing effects on Kv channels, up-regulating the current amplitude, while leading to a decrease in voltage sensitivity (7, 18).…”
mentioning
confidence: 99%